1960
DOI: 10.1042/bj0750487
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insulin in vitro on the accumulation of amino acids by isolated rat diaphragm

Abstract: SYNTHESIS 4875. Magnesium can be totally replaced by manganese in the medium.We are grateful to the Council of Scientific and Industrial Research, New Delhi, for sponsoring the project and for a Fellowship to one of us (P. K.M.), and to Professor B. C. Guha for his kind interest in the work. The skilled technical assistance of Mr D. K. Bose is appreciated. We are also grateful to Dr N. C. Ganguli for useful criticism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
1

Year Published

1962
1962
1980
1980

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 17 publications
9
34
1
Order By: Relevance
“…Insulin, which has been reported to accelerate the uptake ofamino acids by rat diaphragm (Manchester & Young, 1960), had no effect on the removal of glutamate from the perfusion medium or on the synthesis of glucose when-added as a single dose of 0'075unit/ml. at 40min.…”
Section: Methodsmentioning
confidence: 96%
“…Insulin, which has been reported to accelerate the uptake ofamino acids by rat diaphragm (Manchester & Young, 1960), had no effect on the removal of glutamate from the perfusion medium or on the synthesis of glucose when-added as a single dose of 0'075unit/ml. at 40min.…”
Section: Methodsmentioning
confidence: 96%
“…The passage of amino acids into cells by means of carriermediated transport mechanisms is well established in other tissues (Neame, 1968). In the case of muscle, some in vitro work has shown that for a few amino acids entry is by carrier-mediated transport (Manchester & Young, 1960;Akedo & Christensen, 1962;Bombara & Bergamini, 1968). (%) [14C]L-Phenylalanine The present work shows that for some amino acids carrier transport is operating in the living animal, for there is firm evidence that L-lysine and L-threonine enter muscle by an active mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Since results with these two methods were in very good agreement, the boiling water technique was used for all future work. When incorporation of amino acids into tissue protein was being studied as well as amino acid uptake, the cell debris was taken up in 5% trichloroacetic acid, and the isotopically labeled tissue protein prepared and counted according to previously described techniques (13,14).…”
Section: Methodsmentioning
confidence: 99%